Impact of Green Credit Policies on Green innovation in Low-Pollution Industries - Guo, Jiaxin (Transactions on Economics, Business and Management Research, 2024)
This paper addresses the fundamental role of green innovation (GI) in tackling environmental pollution and carbon emissions, emphasizing the pivotal role of green credit policy (GCP) in the market-driven allocation of GI resources. Historically, green credit (GC) has predominantly targeted high-pollution industries (HPI), often neglecting low-pollution industries (LPI). As the scale of GC in HPI stabilizes, the growth rate of their GI is expected to decelerate, highlighting LPI as potential key areas for GC and GI. Utilizing the 2016 "Guiding Opinions on Building a Green Financial System" as a quasi-natural experiment, this study employs a difference-in-differences model to assess the impact of GCP on GI in LPI. The findings reveal a significant improvement in GI in LPI post-implementation of the "Guiding Opinions," compared to ordinary industries. However, challenges such as quantity improvement without quality enhancement and innovation lag remain. This study makes two key contributions. Firstly, it re-evaluates the impact of GCP on GI in HPI by excluding green environmental protection enterprises (GEPE) and HPI enterprises. Secondly, it fills the research gap regarding the impact of GCP on LPI.